2006
DOI: 10.1097/01.nmd.0000198138.41709.4f
|View full text |Cite
|
Sign up to set email alerts
|

Affect Regulation in Borderline Personality Disorder

Abstract: Although difficulty with affect regulation is generally considered a core component of borderline personality disorder (BPD), surprisingly little research has focused on the nature of affect regulation and dysregulation in BPD. A random national sample of 117 experienced clinicians provided data on a randomly selected patient with BPD (N = 90) or dysthymic disorder (DD; N = 27). Clinicians described their patients using the Affect Regulation and Experience Q-sort-Questionnaire Version, a psychometric instrumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(119 citation statements)
references
References 41 publications
8
106
0
2
Order By: Relevance
“…Affective dysregulation is considered a core feature of BPD [7,8,9]. The most prominent model for affective dysregulation in BPD is based on the theory of Linehan and Kehrer [10].…”
Section: Figmentioning
confidence: 99%
“…Affective dysregulation is considered a core feature of BPD [7,8,9]. The most prominent model for affective dysregulation in BPD is based on the theory of Linehan and Kehrer [10].…”
Section: Figmentioning
confidence: 99%
“…1 Current affiliation: Department of Neuroscience and Menninger Department of Psychiatry and Behavioral Sciences, Baylor College of Medicine,Houston TX 77030 responses to irrelevant affective stimuli is critical to navigating a complex environment. Indeed, increased susceptibility to affective triggers has been implicated in the etiology and maintenance of major psychiatric disorders, including depression (e.g., Beauregard et al, 2006;Chiu and Deldin, 2007;Elliott et al, 2002;Holmes and Pizzagalli, 2007;Holmes and Pizzagalli, 2008;Johnstone et al, 2007), post-traumatic stress disorder (e.g., Frewen and Lanius, 2006;Price et al, 2006), and borderline personality disorder (e.g., Conklin et al, 2006;Johnson et al, 2003). Toward the aim of elucidating how emotional response monitoring may be perturbed in psychopathology, the primary goal of the present work was to examine the timecourse and regional specificity of neural processes involved in response inhibition to emotional cues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no significant association with the BDI score emerged in the BPD group. In keeping with previous results [20,21,22], we assume that ED is associated with BPD-related symptoms, and accompanied by general symptom distress, to a greater degree than with depressive symptoms. In the group without BPD, small to moderate association appeared between the scores of the ED Scale and scores on several subscales of the BPDSI-IV as well as scores on the GSI and the BDI, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…This is in line with the findings by Koenigsberg et al [19] that individuals with BPD report greater lability in anger and anxiety compared to individuals with other personality disorders. Conklin et al [20] found that BPD individuals scored just as high on negative emotions as individuals with dysthymia, but were additionally characterized by emotion dysregulation (ED) [19]. The study of Yen et al [21] suggests that self-reported ED is associated with symptoms of BPD to a greater extent than do high negative emotions.…”
Section: Introductionmentioning
confidence: 99%